Factors Affecting Creativity In English As a Second Language Tertiary Students' Writing - Lee, Poh Le (2005)
Tertiary student writers, learning English as a second language (ESL), use reading and writing strategies in the process of writing. Does intervention with the explicit teaching about the Top-Level Structure (TLS) benefit these student writers in the use of strategies? This study on 182 ESL tertiary student writers revealed that there was performance gain after intervention with the explicit teaching about the Top-Level Structure (TLS). The performance of 93 (24 male, 69 female) tertiary students in the treatment group was compare with 89 (31 male; 58 female) tertiary students in the control group. The treatment group was explicitly taught about the TLS through the creative problem solving (CPS) approach for ten weeks. In the course of the ten weeks, the treatment group practised using the TLS in their reading and writing tasks; while the control group was not taught to do so. The result of the post-test means adjusted by pre-test using the ANCOVA showed that there was a significant difference between the two groups. favouring the treatment group. It may be implied that the tertiary student writers in the treatment group had beneficially use the TLS in their writing task, comprising story writing and response writing.